Writing Anxiety: An Investigation Toward EFL Secondary Students’ in Indonesia: Kecemasan Menulis: Investigasi Terhadap Siswa Sekolah Menengah EFL di Indonesia - Rizki Nurfida Pambayun (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research investigated the issues and causes of writing anxiety among EFL secondary school students in Indonesia. There are 15 EFL secondary students in Indonesia participated in this research. The research instruments applied were a questionnaire and an interview. The data was analyzed by using four procedures: data collection, data reduction, data presentation, and conclusion. The researcher finds that the majority of anxiety of secondary students’ is cognitive anxiety. Data showed in data reduction that thirteen of the interviewees have cognitive anxiety in writing class and two more have somatic anxiety and cognitive anxiety. The factors that cause cognitive anxiety are the students' confusion, difficulty, and less interest in writing class. Students who have cognitive anxiety claim that they have difficulties in grammar and vocabulary. Then, students who also indicated somatic anxiety is caused by less confidence in their paper, have a negative perception that if they make a mistake in their paper, such as being wrong in word, phrase or paragraph arrangement. So, it can be concluded that most of the students had anxiety in writing then they need more practice to build their confidence in the writing class.